How to make the EU affairs more attractive? Case study teaching at Czech universities - Kočí Kateřina; Votoupalová Markéta (Politics in Central Europe, 2023)
The article examines the case study (CS) method of teaching the studies focusing on the European Union (i.e. EU studies) through the lenses of the current debates on the EU’s future which stress the growing cleavage and diversity inside and outside the EU. It is then difficult to present these topics to university students via traditional means, or via existing CS on international relations or EU affairs which are often of Western origin, and thus not always easily transferred to other environments. Its aim is to explore how the CS may be enriched by bringing local narratives. The article investigates the Czech Republic, a relatively newer member of the Union, where the EU studies has suffered from declining interest from students over the last few years. Particularly by employing questionnaires and semi ‑structured interviews with Czech university teachers, we examine the type of CS, the extent to which they are and may be applied as a learning method and what their benefits are towards students, teachers and EU studies as a discipline. Our findings suggest that CS are used by the majority of respondents, but confusion prevails over the way CS should be employed. Moreover, the broader context of the CS learning method is rather neglected. Hence, there is space for greater systematic preparation and possibly for CS templates and samples that can be shared by instructors.